Promotion strategies in Perbadanan Perpustakaan Awam Selangor (PPAS) / Siti Hajar Baharin - Baharin, Siti Hajar (2010)
Promotion, as Kotler & Armstrong (1999) point out, is not just advertising but also a form of communication that exists in positive or negative manner in every contact a patron has with an institution. It includes utilizing persuasive information about library services, what library have and what library can provide to user in various activities such as exhibition. In order to promote the library, promotional strategies plan need to be done effectively. The problem aroused to the libraries promotion was the awareness among users about the existence of promotional program and promotional tools. The purpose of this study is to identify the promotional strategies in Perbadanan Perpustakaan Awam Selangor (PPAS) in attracting and encouraging the public users to come to the library frequently. This study focuses on the promotional strategies, promotional constraints and promotional channels that being used by PPAS. A case study approach that combined two data collection methods: (i)interviews; (ii)document analysis methods was used in collecting data. Qualitative data was collected through in-depth guided interviewed from two different groups of respondents consists of PPAS Librarians and PPAS users in different time. Documents were analyzed on different program from time to time. The findings indicated that promotional strategies at PPAS have been developed from time to time starting from the rebranding process in the year 2009. PPAS have been using many channels included banner, bunting, radio, exhibition and promotional program such as 'Information Day' and 'Book Fair'. However, PPAS had faced several promotional constraints included limited budget, time constraints and lack of staff. Therefore, several recommendations had been proposed to PPAS: (a) identifying the date, objectives, target segments and messages that need to be delivered strategically; (b) creatively and aggressively utilizing the promotional channels; (c) had two stages of evaluation, before and after the program; (d) try to get extra funds from the government to promote the library. This study was benefiting PPAS in improving their promotional strategies in future. Only by having effective promotional activities and referring towards all the previous and current study on particular issues could help PPAS to identify and determined their strengths and weaknesses